A SOFTWARE FOR EVALUATION OF LUMBAR SPINE COMPUTED TOMOGRAPHY DENSITOMETRY - Kolpinskiy, G.I.; Zakharov, I.S.; Ushakova, G.A.; Ushakov, A.V.; Ivanov, V.I.; Kagan, E.S. (Fundamental and Clinical Medicine, 2016)
Aim: To develop a software for evaluation of lumbar spine computed tomography densitometry to predict the risk of osteoporotic fractures in postmenopausal women. Materials and Methods: We evaluated the lumbar spine computed tomography densitometry data in 282 postmenopausal women following a computerized modeling Results: The sensitivity and specificity of the model were 77.8% and 86.7%, respectively, with the area under the ROC curve of 0.894 (95% confidence interval 0.855-0.932). We have also developed an original software for prediction of osteoporotic fractures in postmenopausal women. Conclusion: Our software can assist the clinicians in predicting the risk of osteoporotic fractures in postmenopausal women.